Ganglioside and Non-ganglioside Mediated Host Responses to the Mouse Polyomavirus. - John You; Samantha D O'Hara; Palanivel Velupillai; Sherry Castle; Steven Levery; Robert L Garcea; Thomas Benjamin (PLoS Pathogens, 2015)
Gangliosides serve as receptors for internalization and infection by members of the polyomavirus family. Specificity is determined by recognition of carbohydrate moieties on the ganglioside by the major viral capsid protein VP1. For the mouse polyomavirus (MuPyV), gangliosides with terminal sialic acids in specific linkages are essential. Although many biochemical and cell culture experiments have implicated gangliosides as MuPyV receptions, the role of gangliosides in the MuPyV-infected mouse has not been investigated. Here we report results of studies using ganglioside-deficient mice and derived cell lines. Knockout mice lacking complex gangliosides were completely resistant to the cytolytic and pathogenic effects of the virus. Embryo fibroblasts from these mice were likewise resistant to infection, and supplementation with specific gangliosides restored infectibility. Although lacking receptors for viral infection, cells from ganglioside-deficient mice retained the ability to respond to the virus. Ganglioside-deficient fibroblasts responded rapidly to virus exposure with a transient induction of c-fos as an early manifestation of a mitogenic response. Additionally, splenocytes from ganglioside-deficient mice responded to MuPyV by secretion of IL-12, previously recognized as a key mediator of the innate immune response. Thus, while gangliosides are essential for infection in the animal, gangliosides are not required for mitogenic responses and innate immune responses to the virus.